The Characteristic Features of Pregnant Women who Experience Chronic Lack of Energy in Pregnant Women: Gambaran Karakteristik Ibu Hamil yang mengalami Kurang energi Krois (KEK) pada Ibu Hamil - Ikrawati, Ikrawati; Tempali, Sri Restu (Napande: Jurnal Bidan, 2023)
Introduction: Chronic Energy Deficiency (CED) during pregnancy will cause problems, both for the mother and the fetus. CED in pregnant women can cause risks and complications for the mother, including anemia, bleeding, the mother's weight does not increase normally and infection. The Kamonji Health Center in the last 2 years has seen an increase in the number of KEK sufferers. Data for January-May 2023 out of 483 pregnant women who had KEK were 62 people (12.83%). The aim of this study was to describe the characteristics of pregnant women who experience Chronic Energy Deficiency (KEK) in the working area of ​​the Kamonji Health Center, Palu City. This Method type of research is descriptive research. The population in this study of pregnant women with CED was 62 people. The number of samples is 38 people. The sampling technique is simple random sampling. The analysis used was univariate analysis. The results showed that 30 people (78.94%) had good knowledge about Chronic Energy Deficiency (KEK), and 8 people (21.06%) had poor knowledge. Body Mass Index (BMI) was normal for 29 people (76.31%), Body Mass Index (BMI) was abnormal for 9 people (23.69%). 26 people (68.42%) had good Upper Arm Circumference (LiLA), 12 people (31.58%) had poor LiLA.In conclusion, most of the respondents had good knowledge about KEK, most of them had normal BMI and most of them had good knowledge of LILA. It is recommended that the Kamonji Health Center improve health promotion through leaflets on preventing SEZs in pregnant women.